Azohydromonas caseinilytica sp. nov., a Nitrogen-Fixing Bacterium Isolated From Forest Soil by Using Optimized Culture Method - Dahal, Ram Hari; Chaudhary, Dhiraj Kumar; Kim, Dong-Uk; Kim, Jaisoo (Frontiers in Microbiology, 2021)
A bacterial strain, designated strain G-1-1-14T, was isolated from Kyonggi University forest soil during a study of previously uncultured bacterium. The cells of strain G-1-1-14T were motile by means of peritrichous flagella, Gram-stain-negative, rod-shaped, and able to grow autotrophically with hydrogen and fix nitrogen. Phylogenetic analysis based on 16S rRNA gene sequence indicated that strain G-1-1-14T belonged to the genus Azohydromonas. The closest species of strain G-1-1-14T were Azohydromonas ureilytica UCM-80T (98.4% sequence similarity), Azohydromonas lata IAM 12599T (97.5%), Azohydromonas riparia UCM-11T (97.1%), and Azohydromonas australica IAM 12664T (97.0%). The genome of strain G-1-1-14T was 6,654,139 bp long with 5,865 protein-coding genes. The genome consisted of N2-fixing genes (nifH) and various regulatory genes for CO2 fixation and H2 utilization. The principal respiratory quinone was ubiquinone-8, and the major polar lipids were phosphatidylethanolamine, diphosphatidylglycerol, and phosphatidylglycerol. The major fatty acids were summed feature 3 (iso-C15:0 2-OH and/or C16:1ω7c), C16:0, summed feature 8 (C18:1ω7c and/or C18:1ω6c), and cyclo-C17:0. The DNA G + C content was 69.9%. The average nucleotide identity (OrthoANI), in silico DNA–DNA hybridization (dDDH), and conventional DDH relatedness values were below the species demarcation values for novel species. Based on genomic, genetic, phylogenetic, phenotypic, and chemotaxonomic characterizations, strain G-1-1-14T represents a novel species within the genus Azohydromonas, for which the name Azohydromonas caseinilytica sp. nov. is proposed. The type strain is G-1-1-14T (= KACC 21615T = NBRC 114390T).